PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dini Susmiandini; Siti Khodijah (Universitas La Tansa Mashiro, 2016)
Profitability ratio is the ratio to measure financial performance. One indicator of the profitability ratio that I use is Return On Assets (ROA). Return On Assets (ROA) is a measure of the effectiveness of management in generating profits by managing its total assets. While the factors that support success to get the Return On Assets (ROA) is the working capital turnover and inventory turnover. This research was conducted in order to determine the effect of working capital turnover and inventory turnover on Return On Assets (ROA) in the pharmaceutical company listed on the Indonesia Stock Exchange 2010-2015 period. The data used is secondary data with the method of documentation in the form of annual financial statements. The population in this study amounted to 10 pharmaceutical companies and samples taken using purposive sampling is that there are 6 companies sampled. Analysis technique used is linear regression, Classical Assumption Test and Testing Hypotheses with use SPSS 20. Based on the test results F is known that the significance value less than 0.05 is equal to 0.000 which showed that simultaneous rotation of working capital and inventory turnover have a significant effect on Return On Assets (ROA). And based on t test results showed that the partial rotation of working capital significance effect on Return On Assets (ROA) with significantly smaller than 0.05 is 0.000. Based on t test also showed that the partial inventory turnover have a significant effect on Return On Assets (ROA) with significantly smaller than 0.05 is equal to 0.000.